Buying search, buying students: how elite U.S. institutions employ paid search to practice academic capitalism online. Issue 2 (2nd July 2020) - Taylor, Z. W.; Bicak, Ibrahim
ABSTRACT: While academic capitalism pervades many facets of US higher education, this study analyzes paid adwords as a method of academic capitalism in the online marketplace. This article presents findings from a five-month quantitative analysis of paid adwords of the 2018 top US News & World Report top 100 national universities. Capturing the Fall 2017 application season, this study investigated how many, when, and what adwords institutions purchase and how cost efficient these adwords were by words-per-click and price-per-click. Data indicate private institutions buy more adwords and pay a greater amount than public institutions but do not generate more traffic from these adwords. Regression analyses find better-ranked institutions generate more traffic from adwords than lower-ranked peers, but similar analyses predicting adwords and cost were not statistically significant. These findings suggest a stratified Internet marketplace, with better-ranked institutions practicing academic capitalism to drive web traffic toward their websites during application season.